The deciphering stimulus of a compound word: the problem of definition and description - Andrey I. Brovets (Russian Language Studies, 2019)
The article discusses the concept of abbreviated decryption of stimulus, which refers to a method of rolling out a contracted construct abbreviation in an equivalent phrase. The study is relevant because it implements and describes a new approach to abbreviation interpretation, stating that a complex word in a synchronous section of the language usually corresponds not to not, but to several equivalent phrases that appear as a result of actualizing alternative decryption stimuli of a contracted abbreviation construct in the text, while existing dictionaries of complex words give only one phrase as an equivalent, usually with a relative adjective. The purpose of the article is to define and describe the system of decoding stimuli of abbreviations in the Russian language. The novelty of this study lies in the fact that it states the existence of a branched system of equivalent phrases in the language, where parallel multiple decryption of a contracted construct of the abbreviation is carried out. The practical significance of the results is the possibility to use them in compiling dictionaries of abbreviations, as well as in translating and editing. The article describes two principles of interpreting decryption stimuli - cognitive and formal. It is concluded that cognitive bases of allocating decryption stimulus are associated with such parameters as stereotypy, uniqueness, regularity. Under the decryption stimulus in this case we understand background knowledge, provoking a particular variant of rolling out a contracted construct of the abbreviation, the stereotype of its explication. As a result of the study, we found that a presentative decryption stimulus is the most stereotyped one. The formal approach defines the decryption stimulus as specific, i.e. empirically observed equivalent phrase in the form of a contracted construct abbreviation in the texts. The perspectives of further research in this area is clarification of the classification of decryption stimuli and on its basis methods of their forecasting.